Circulating microrna-22 as a biomarker related to oxidative stress in hypothyroid women patient - Abd, Zahraa Mohammed Ali; Khinteel Jabbar, Nawal (Vojenské zdravotnické listy, 2024)
Background: Recent research has linked the spread of microribonucleic acid (miRNA) to numerous disorders, either as a stimulant or an inhibitor. One of these is miRNA-22, which research has connected to oxidative stress and thyroid issues. However, the underlying mechanisms are unknown. This study investigates the expression of miRNA-22 in hypothyroid women and its relationship to the rise in oxidative stress in the patient population.Materials and Methods: 40 women patients with Hypothyroid and 40 in this study, healthy volunteers who served as controls were included. The levels of serum luteinizing hormone (LH), follicle-stimulating hormone (FSH), and thyroid-stimulating hormone (TSH) were measured by sandwich assay, while free triiodothyronine (FT3) and thyroxine (T4) levels were measured competitive binding immunoenzymatic assay. To assess lipid profiles, an automated analyzer was employed. By enzyme-linked immunosorbent assay (ELISA), Interleukin 6 (IL-6) levels were measured. Malondialdehyde (MDA), superoxide dismutase activity (SOD), catalase activity (CAT), and advanced oxidation protein products (AOPPs), and assessed using a colorimetric technique. The quantitative polymerase chain reaction was used to evaluate the expression of serum miRNA-22.Results: Significantly more SOD and CAT activity was identified in patient groups than in the control group (P<0.05), also the patient group's AOPP and MDA concentrations were discovered to significantly outweigh those of the control group. (P< 0.05). IL-6 levels were significantly higher in the patient group than in (P<0.05) the control group. The level of miRNA-22 was higher in the sick group as compared to the control groups (P<0.05).Conclusions: The pathophysiology of oxidative stress brought on by hypothyroidism involves miRNA-22 expression, there is a reciprocal relationship between the increase in gene expression of the miRNA-22 and the increase in oxidative stress, which results in the disease's development.
Keywords: oxidační stres; hormony; MicroRNAs; biologické markery; Biomarkers; spektrální analýza; Spectrum Analysis; mikro RNA; Adult; Chemistry Techniques, Analytical; dospělí; Hormones; lidé; ženské pohlaví; chemické techniky analytické; Hypothyroidism; Humans; Female; Oxidative Stress; hypotyreóza